Analisis Hasil Belajar Bahasa Arab Siswa Kelas VIII Madrasah Tsanawiyah Al-Zaytun Indramayu Berdasarkan Kebiasaan Belajar Tahun 2024 - Nurul Fauziah; Irvan Iswandi; Mas’ud Arifin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to analyze the Arabic language learning outcomes of class VIII students at Madrasah Tsanawiyah Al-Zaytun Indramayu based on study habits. The research approach used is qualitative, with data collection methods through observation, interviews, documentation and questionnaires involving Arabic teachers, students and dormitory administrators. Based on the research results, it was found that student learning outcomes were in the good category with an average score of 90, as measured through daily tests. Student study habits are demonstrated through discipline in preparation and attendance in class. However, there are several aspects of study habits that require improvement, such as structured study routines, deeper understanding of the material, interest in reading, and effective note-taking habits. Overall, student learning outcomes remain in the good category.